Prevention of crime in housing through environmental planning / Ida Noorjulianti Sugijanto - Sugijanto, Ida Noorjulianti (2004)
Various factors influence the occurrence of crimes such as biological, imbalanced social and economic distribution and psychological factors, but if there are principles in physical planning which can reduce or prevent crimes then the public and professionals as well as decision makers should be made aware and educated on these principles. It is then their responsibility to consider these principles in their preliminary planning. This paper intends to instill awareness amongst local environmental co-creators, decision makers and the general public of the importance of addressing secure and safe design in their preliminary planning stage. It also highlights possible environmental planning principles formed on the basis of 'territoriality' and 'defensible space' that could contribute towards crime prevention in housing. Due to space limitations, this paper discusses only Crime Prevention Through Environmental Design (CPTED) principles related to physical planning inclusive of a brief case study of one of the local housing crime 'hot-spots' in Negeri Sembilan.